Iowa Birdline update, August 10, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for August 10, 1992. Highlights of the update include sightings of the continued presence of the juvenile Laughing Gull and two Western Grebes. Also included are handwritten notes for the next week's update with sightings of a possible Black Vulture and a confirmed sighting of a Ruddy Turnstone. Epson - sheet feed/flatbed